Epidemiology of Mortality From Cerebrovascular Accident in Patients Admitted to Sina (Farshchian) Educational-Medical Hospital of Hamadan in 2018-2019 - Mehrdad Maleki Jamasbi; Hiva Azami; Hadis Ebrahimi Neshat; Kamran Alipoor; Payam Karimian (Shahrekord University of Medical Sciences, 2022)
Background and aims: Cerebrovascular accidents are a major cause of death and disability in many countries. Therefore, the epidemiological indicators are highly important in the case of these patients' mortality. The present study aimed to determine the epidemiology of mortality due to cerebrovascular accidents in patients admitted to Sina (Farshchian) hospital of Hamadan within 2018-2019. Methods: In this descriptive cross-sectional study, data of deceased patients were collected from one-year medical records in the neurology wards of Sina (Farshchian) hospital in Hamadan using the census method and a researcher-made checklist. The exclusion criteria were the cause of death except for cerebrovascular accident and incompleteness of data in patient's medical record. Data were analyzed by descriptive statistical methods and SPSS 21. Results: Out of the 1196 patients admitted to the neurology wards, 159 cases died, and this rate was nearly equal between men and women. The highest mortality frequency belonged to ischemic type (83%), people over 60 years old (83%), illiterate (77.4%), urban (69.2%), self-employed (42.8%) individuals, and those with a history of underlying disease (73.6%), no history of smoking (90.6%), previous stroke (78.6%), and family history of stroke (99.4%). Conclusion: The findings of the present study showed that certain groups such as the elderly, illiterates, urban residents, self-employed, and people with underlying diseases had a higher mortality rate due to cerebrovascular accidents. Thus, special attention to these groups in health planning can be efficient in reducing the mortality of these accidents.